Survival and success rate of one-piece implant inserted in molar sites - Francesco Carinci (Wolters Kluwer Medknow Publications, 2012)
Background: Recently, the use of one-piece implants (OPI) has become more popular. Since no reports specifically focus on OPIs inserted in molar areas, a retrospective study has been performed. Materials and Methods: A series of 36 OPIs (Diamond; BIOIMPLANT, Milan, Italy) were inserted into the molar area of patients admitted at the Dental Clinic, University of Chieti, Italy, for oral rehabilitation between January and December 2010. Results: In our series survival rate (SVR) and success rate (SCR) were 91.7% and 97%, respectively. Statistical analysis demonstrated that no studied variable has an impact on survival (i.e., lost implants) as well as on clinical success (i.e., crestal bone resorption). Conclusion: OPIs are reliable devices for oral rehabilitation in the molar areas.